Bacterial Contamination and Physicochemical Analysis of Different Water Sources in Enugu Metropolis, Enugu State, Nigeria - Ozoffor Chinedu Habakkuk (Sokoto Journal of Medical Laboratory Science)
Water is a very important part of human diet. However, many water sources in developing countries are contaminated, making it unsafe for human consumption. Pathogens such as Escherichia coli and coliforms are indicators that the water is faecally contaminated and can cause outbreak of cholera, typhoid, and other related diseases. Heavy metals have been identified as one of the water contaminants which pose health hazards to the consumers. This study was conducted to assess the physicochemical analysis of different water sources in Enugu metropolis, Enugu state Nigeria. This study was conducted to assess the bacterial contamination of different water sources in Enugu metropolis, Enugu state, Nigeria. A total of 150 samples of water (tanker, stream and well water samples) from different areas such as Camp, Abakpa, Obiagu, Trans-Ekulu, Ituku, 9th Miles Corner, Awkunanaw, Asata and Uwani. Modified multiple tube fermentation techniques, Gram stain reaction, Motility test, Biochemical tests were carried out. Metals and heavy metals were identified accordingly. The physicochemical values for water samples: pH, colour, total dissolved solids, Sodium, Lead, Magnesium, Cadmium, Arsenic, electrical conductivity, sulphate, chloride were determined. The stream water samples contained the highest concentration of chemicals and leading in physical parameters. There were statistically significant difference (p<0.05) among them. Organisms isolated in decreasing order of occurrence were Escherichia coli, Pseudomonas aeruginosa, Enterobacter sp., Klebsiella sp., Aeromonas sp., Bacillus sp. and Proteus sp. The studies showed that well, stream and tanker water were contaminated with microorganisms, physical and chemical contaminants.